IMPROVING STUDENTS’ LEARNING OUTCOMES THROUGH THE MEDIA OF SUNDA MANDA TRADITIONAL GAME - Dinar Ayu Mirunggan Sari; Murtono Murtono (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
This study aimed to improve students’ learning outcomes through the media of Sunda Manda game. This study was Classroom Action Research (CAR) based on Kemmis and Mc. Taggart which included two cycles. Each cycle consisted of three meetings with four stages namely planning, implementing, observing, and reflecting. This study was conducted at grade IV elementary school involving 37 students as the research subjects. Data were collected through observation, interview, and documentation. Then, the analysis of the data of this research was conducted by using interviews, questionnaires, and documentation. The result of this study showed an increase in students’ learning outcomes. Findings revealed that in Cycle I, 26 students reached the target score with an average of  72.76 (70.27%) for social science and 25 students reached the target schore with an average of 73.49 (67.57%) for Bahasa Indonesia.. Then, in Cycle II, 34 students reached the target with an average of 80.21 (91. 89%) for social science, and 32 students reached  the target with an average of 79,51 (86,49%) for Bahasa Indonesia. Furthermore, the average score of the learning outcomes for the affective aspect in Cycle I was 74.38 (61.98%) and it increased to 96 (80.00%) in Cycle II. In addition, the learning outcomes for skills in Cycle I was 51.76 (61.62%) and it increased to 66.84 (79.57%) in cycle II. This research implied that the innovation of media like Sunda Manda traditional game improved the learning outcomes of students at grade IV elementary school. Thus, it was concluded that there was an increase in the students’ learning outcomes through the media of Sunda Manda traditional game.